Ceric Ammonium Nitrate Oxidation of Cinnamic Ester Derivatives for the Synthesis of Benzaldehydes - Sridhar Rao1, A.; Shankara Chary1, J.; An, M. (Asian Journal of Chemistry, 2013)
The preparation of aldehydes by oxidative cleavage of carbon-carbon double bonds is a useful reaction. But the problem is of getting good yields and requires drastic reaction conditions. Cinnamic ester derivatives yield correspondingly substituted benzaldehydes when oxidized by ceric ammonium nitrate under mild conditions with acetonitrile in moderate to good yields is described. In the present paper a simple and effective method for synthesis of benzaldehydes using ceric ammonium nitrate is described in the light of existing literature.